The Development and Validation of the Christian Environmentalism Scale (CES) from a Philippine Sample - Baring, Rito V. (Journal of empirical theology, 2021)
Responding to emerging ecotheologies, we articulated a new environmental construct distinct from previous environmental measures which largely follow developmental models. In the present study we developed and reviewed the psychometric properties of the Christian Environmentalism Scale (CES) initially in three dimensions from 970 youth participants in the Philippines. Study design included exploratory and confirmatory factor analysis for data reduction and best fit model analysis. CES is a unidimensional 15-item measure with a high internal consistency (Cronbach’s alpha = .95) score and adequate results for best fit model. CES had significant associations with pro-environment and religious attitude scales indicating initial evidence of convergent validity.